2018
DOI: 10.4172/2329-891x.1000289
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Mortality in Tuberculosis Patients at Debre Birhan Referral Hospital, Ethiopia: A Retrospective Study

Abstract: Background: Tuberculosis (TB) is the major cause of mortality worldwide and deaths from tuberculosis continue to occur despite the availability of effective antimicrobial agents. Understanding the factors associated with death is important to decrease mortality from TB. Hence, the aim of this study was to assess the magnitude and factors leading to death among TB patients registered at Debre Birhan Referral Hospital, Debre Birhan, Ethiopia.Methods: This is a retrospective cross-sectional study. Data was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…In contradiction to this finding, other studies reported that the place of residence was not significantly associated with death. 15,23 In the present study, patients aged ≥45 years (HR = 5.32, 95% CI: 1.23-22.96) had a lower survival rate as compared to the younger age groups. A wider confidence interval of hazard ratio for age was observed.…”
Section: Discussionmentioning
confidence: 47%
“…In contradiction to this finding, other studies reported that the place of residence was not significantly associated with death. 15,23 In the present study, patients aged ≥45 years (HR = 5.32, 95% CI: 1.23-22.96) had a lower survival rate as compared to the younger age groups. A wider confidence interval of hazard ratio for age was observed.…”
Section: Discussionmentioning
confidence: 47%
“…The proportion of the EPTB varied from 8% [26] to 25% [60]. With regard to HIV infection status among TB patients, the HIV-positive ranged from 2% [25] to 44% [53], HIVnegative ranged from 4% [27] to 95% [24], and unknown HIV status ranged from 1% [24] to 90% [27].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%